Process Improvement for the Continuous Synthesis of N-Benzylhydroxylamine Hydrochloride - Xiaoguang Chen; Ke Chen; Guoxian Cai; Haoyue Xiang; Kai Chen; Hua Yang (Chemistry, 2025)
N-Benzylhydroxylamine hydrochloride serves as a critical intermediate in organic synthesis, yet traditional synthesis methods often face significant safety risks and high production costs. In this work, we developed a continuous synthesis process for N-benzylhydroxylamine hydrochloride, achieving an overall yield of 75% under mild and safe reaction conditions. Additionally, the implementation of solvent recovery and the recycling of hydroxylamine hydrochloride reduced the production cost to approximately $10 per kilogram. These advancements underscore the economic and practical viability of this method for large-scale industrial applications.